Analisis Kinerja Karyawan Melalui Kepuasan Kerja, Kompensasi, dan Displin Kerja Pada Karyawan L’Avenue Office & Residences - Annisa Zahra Putrie; Yosafat Puji Hastoko (CV. ULIL ALBAB CORP, 2023)
This study intends to determine whether the analysis of employee performance at L'Avenue Office & Residences has an impact on job satisfaction, compensation, and work discipline. In this research using accidental sampling research technique with non-probability sampling. L'avenue office & residences employees as many as 100 people who can be used as a sample of those who happen to meet with researchers are considered as a reliable source of data. This research method is quantitative research using multiple linear regression analysis techniques. The results of this study show that job satisfaction has no effect on employee performance, compensation has no effect on employee performance, work discipline has a significant effect on employee performance at L'avenue offices & residences. But simultaneously these three variables have a significant effect on employee performance at L'avenue office & residences